Sentiment Analysis of Chinese R&B Music Album Short Reviews Using SKEP Topic Model - Xiao, Sa (Transactions on Computer Science and Intelligent Systems Research, 2024)
In the current online environment, music reviews can be a good reflection of the popularity of the music, which can attract others to listen and pay attention to the music. A sentimental analysis of these reviews and the identification of emotional attitudes are essential for the dissemination of music. Based on the classic Chinese R&B album "David Tao" and its related reviews, this paper aims to analyze sentiment tendencies, analyze word frequency, and extract comment topics based on the Baidu AI Cloud interface of the SKEP algorithm. Research has found that listeners have a relatively positive emotional attitude towards this album, with positive reviews accounting for about 85%, and the reviews cover a variety of hot topics. The album’s popularity, word-of-mouth evaluation, influence and other indicators all show a high level, highlighting that this album indeed provides a certain direction and strategy for the development of Chinese R&B. The charm of the album’s musical style has been fully reflected and attracted widespread attention and recognition. It not only injects new vitality into the development of Chinese R&B music, but also provides valuable reference and inspiration for those interested in this music style. The research in this article emphasizes the important role of music in cultural inheritance and innovation, and also provides useful reference and guidance for the sustainable development of the music industry.